Time to Euthyroidism and Its Determinants Among Thyrotoxicosis Patients on Anti-Thyroid Drug Who Attend to Medical and Ambulatory Clinics of South Tigrai General Hospitals - Maldey H; Tadesse S; Alem AZ; Hagezom HM; Hagos Gufue Z (Dove Medical Press, 2021)
Hiluf Maldey,1 Sumeya Tadesse,2 Adugnaw Zeleke Alem,3 Haftamu Mamo Hagezom,4 Zenawi Hagos Gufue5 1Department of Clinical Pharmacy, College of Medicine and Health Sciences, Adigrat University, Adigrat, Ethiopia; 2Department of Clinical Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Epidemiology and Biostatistics, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 4Department of Psychiatry, College of Medicine and Health Sciences, Adigrat University, Adigrat, Ethiopia; 5Department of Public Health, College of Medicine and Health Sciences, Adigrat University, Adigrat, EthiopiaCorrespondence: Hiluf Maldey Email redaemaldey354@gmail.comPurpose: To determine the time to euthyroidism and its determinants among thyrotoxicosis patients on anti-thyroid drug attending the medical and ambulatory clinics of South Tigrai General Hospitals, Ethiopia, 2015- 2020.Methods: A multi-center retrospective cohort study was conducted from March 30, 2020, to July 30, 2020, among adult thyrotoxicosis patients who received anti-thyroid medications in the medical and chronic ambulatory clinics of South Tigrai General Hospitals, Ethiopia. Epi-data manager version 3.1 software was used for data entry and then exported to STATA version 15 for windows for analysis. Cox proportional hazards regression model was used to determine the determinants of time to euthyroidism and the summary measures of the adjusted hazard ratio with a 95% CI were presented, and P-value < 0.05 used to declare the statistical significance.Results: One hundred and seventy-five (51.9%) thyrotoxicosis patients become euthyroid with the median time to euthyroidism of 9 months, IQR (6- 12) months, with a total of 5542 person-months of observation. Age greater than 40 years (AHR = 0.7; 95% CI 0.54- 0.96), toxic multi-nodular goiter (AHR = 0.69; 95% CI 0.60- 0.87), World Health Organization goiter size three (AHR = 0.78; 95% CI 0.54- 0.82) and baseline free thyroxin (AHR = 0.96; 95% CI 0.80- 0.99) were the independent determinants of delayed time to euthyroidism.Conclusion: The time to euthyroidism was longer than the expected time. High baseline free thyroxin, toxic multinodular goiter, elderly patients, and patients with World Health Organization goiter size three were determinants of delayed time to euthyroidism.Keywords: thyrotoxicosis, propylthiouracil, euthyroid, South Tigrai, Ethiopia